PENERAPAN PENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY (SETS) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 4 KUNDUR - Haryati '; Elva Yasmi Amran Yasmi Amran; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research aims to improve student achievement on the subject of colloids in class XI Science Senior High School 4 Kundur. This type of research is experimental research study design randomized control group pretest-posttest. Research conducted at Senior High School 4 Kundur. Samples of the research were students of class XI Science 1 as an experimental class and class XI Science 2 as the control class. Experimental class is a class that is applied approach to science, environment, technology and society (SETS) whereas the untreated control class. Data analysis technique used was t test. Based on test data analysis obtained tcount>ttable is 2,33>1,67, meaning that the use of science approach, environment, technology and society (SETS) can increase student achievement on the subject of colloids in class XI Science Senior High School 4 Kundur by category increase achievement (N-Gain) high at 0.71. Key words: Learning Achievement, Approach SETS, Colloid.